Looking beyond glaciers to understand mountain water security - Drenkhan, F.; Buytaert, W.; MacKay, J.D.; Barrand, N.E.; Hannah, D.M.; Huggel, C. (Nature Research, 2023)
Changes in the mountain cryosphere impact the water security of downstream societies and the resilience of water-dependent ecosystems and their services. However, assessing mountain water security requires better understanding of the complex interaction between glacial meltwater and coupled human–natural systems. In this context, we call for a refocusing from glacio-hydrological monitoring and modelling to a more integrated social-ecological perspective of the wider catchment hydrology. This shift requires locally relevant knowledge-production strategies and the integration of such knowledge into a collaborative science–policy–community framework. This approach, combined with hydrological risk assessment, can support the development of robust, locally tailored and transformational adaptation strategies.
Keywords: Mountain cryosphere; Water security; Climate adaptation; https://purl.org/pe-repo/ocde/ford#1.05.00